Navigating the Intersection of Business Competition and Islamic Law: A Legal Study - Faisal Santiago (International Journal of Artificial Intelligence Research, 2022)
This research is based on the need to understand the regulation of business competition in the context of Islamic law, which is an essential aspect in building a just and sustainable economic system in countries with a majority Muslim population. The idea of this article is based on a misguided understanding of business regulations based only on conventional legal practices. At the same time, Islamic law regulates matters related to business competition. Scientific contributions pertain to the discussion of how commercial competition laws should be applied in the context of Islamic law in the modern era. The conclusion drawn from this paper is that it requires criminal provisions and procedures for their implementation. The KPPU institution is also given the authority to confiscate and handle cases. So far, business competition regulations have created a harmful misperception between law enforcers and KPPU as business competition supervisors.